(untitled) (Journal of Economic Research & Business Administration, 2015)
The development of the Kazakhstani market of information technologies in the last decade, largely due to the general economic situation . In the period from the beginning of the independence of Kazakhstan market has grown from scratch , so the high rate of growth were natural . In recent years, the growth rate IT - market decline. The market entered a " mature " stage , which will inevitably lead to increased competition .